Negative interest rates in the euro area: does it hurt banks? - Stráský, Jan (OECD Economics Department Working Papers, 2019)
The negative interest rate policy (NIRP) has been in place in the euro area since June 2014. While the NIRP can provide additional monetary accommodation in the situation where the neutral rate of interest is most likely negative, there are also unintended consequences for banks' profitability and potential financial stability risks associated with this policy. The paper assesses the effect of the NIRP on the net interest rate margins of the euro area banks using quarterly consolidated bank level data for some 50 banking groups directly supervised by the Single Supervisory Mechanism. Since our data set extends to 2018, it allows us to examine the period of negative short-term interest rates separately from the period of low, but positive policy rates. The econometric results confirm the effect of the interest rate level on bank profitability and, in some specifications, also suggest an additional negative effect on bank profitability in the period of negative euro area short-term interest rates. This additional effect of the NIRP is the strongest when looking at the disaggregated components of net interest income, i.e. interest income and interest expense. However, the effects are not particularly robust across various profitability measures and tend to disappear when conditioning on macroeconomic variables, such as expected real GDP growth and inflation expectations. Therefore, in line with other existing studies, we find weak evidence of possible negative effects on bank profitability from keeping rates low for an extended period of time. Statistical analysis of the bank-level data also points to an ongoing compression of non-interest income, in particular for the best performing banks, and a slow recovery in return on total assets among all banks over the analysed period. This Working Paper relates to the 2018 OECD Economic Survey of Euro Area (https://www.oecd.org/economy/euro-area-and-european-union-economic-snapshot/)